ANALYSIS OF EFFECT OF PROFITABILITYAND MANAGERIAL OWNERSHIPON THE TERM OF DELIVERY OF FINANCIAL REPORTON SOE REGISTERED IN INDONESIA 2012 STOCK EXCHANGE 2012-2016 - Indra Lila Kusuma; Avesti Nila Nawangsari (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2017)
This study aims to examine the analysis of the effect of profitability and managerial ownership over the period of submission of financial statements in the stock exchanges of Indonesia. This research uses secondary data with population and sample of financial data of State Owned Enterprise (BUMN) listed in Indonesia Stock Exchange in 2012 until 2016. The analysis technique used is classical assumption test which includes normality test, multicollinearity, heterokedastisitas and test Autocorrelation. Other tests use multiple linear regression test, T test, F test and Coefficient of determination test. The results showed that Profitability and Managerial Owners Influence all on the Period of Submission of Financial Statements.Profitability, Managerial Ownership and Time of Submission of Financial Statement.